Analysis of the Implementation of Science Learning based on Teachers' Technological Pedagogical and Content Knowledge (TPACK) Capabilities - Yanti, M.; Rahayu, D. P.; Rabbani, A. (Universitas Negeri Yogyakarta, 2024)
Teachers play a crucial role in facilitating students' understanding and making science material more accessible. To achieve this, educators must possess the capability to use technology, select appropriate learning models, and possess sufficient knowledge of the material - collectively termed as Technological Pedagogical Content Knowledge (TPACK). Therefore, this research aimed to analyze the implementation of science learning based on the teacher's TPACK ability level. The qualitative descriptive research method was employed, involving three science teachers selected through convenience sampling and identified as Teacher A, Teacher B, and Teacher C. TPACK ability data was obtained using a TPACK measurement questionnaire developed by Shmidt et al., (2009) with a total of 54 statement items with three general dimensions. They are Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK). The analysis involved observing each teacher during science lessons evaluating the alignment of planning and implementation through an observation sheet. The results of the analysis show that teachers with high TPACK abilities also have more complex science learning in terms of material, method, and technology selection. The results of this research can be used as a reference for teachers in designing and applying learning, especially in terms of integrating technology into science learning.